Image Analysis for Spectroscopic Elemental Dot Maps: P, Al, and Ca Associations in Water Treatment Residuals as a Case Study - Zohar, Iris; Haruzi, Peleg (Frontiers in Environmental Chemistry, 2021)
The associations of elements upon a heterogeneous surface may control nutrients or pollutants sorption and release, having agricultural and environmental implications. This chemical behavior can be elucidated by spatial spectroscopy, followed by image analysis. The purpose of this paper is to present a working procedure for image analysis using the free program ImageJ that can be applied for dot maps of three or more elements produced by solid-state spectroscopy. Detailed step-by-step instructions lead to visual and quantitative information regarding elements associations. The working procedure was demonstrated for P, Al and Ca dot maps produced by scanning electron microscopy energy dispersive spectroscopy (SEM-EDS) for surfaces of Al-based water treatment residuals (Al-WTRs), a by-product of drinking water pretreatment with alum coagulant. Al-WTR was reused to adsorb the macro-nutrient P from polluted soil leach (SL) and dairy wastewater (WW). Surficial P onto Al-WTR, SL-Al/O-WTR, and WW-Al/O-WTR (0.56%, 0.93%, and 2.15%, respectively) displayed sorption dynamics, mostly with Al and Ca. Quantification of the spatial proportions of individual elements and their associations indicated P-Al pool > P-Ca pool (45-24% and 17-7%, respectively). Upon introducing P-rich dairy WW, the behavior of P sorption by Al and Ca changed and became more clustered. A ternary phase of P-Al-Ca covered 38% of the area with signal, compared to 4.3% and 4.6% of the area in Al-WTR and SL-Al-WTR, where it was limited to particles edges only. Thus, the presented protocol may promote employing image analysis for geochemical applications, elucidating chemical behavior and affinities. Advantages and pitfalls are discussed.